2018
DOI: 10.1016/j.sjbs.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessing risks of pesticides targeting lepidopteran pests in cruciferous ecosystems to eggs parasitoid, Trichogramma brassicae (Bezdenko)

Abstract: Lethal and sub lethal effects of fresh and old residues of azadirachtin, spinosad, var. ( var. ), and deltamethrin, were evaluated at their recommended field doses against adult and immature stages of under conditions. The experiments were carried out at the Entomology section of Division of Crop Protection, ICAR Research Complex for NEH region, Umiam, Meghalaya, in 2012-2013. The effects of different pesticides were determined by bioassays using the residual film method, the diet contamination method, the pup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
(41 reference statements)
5
14
0
Order By: Relevance
“…Azadirachtin, although a botanical insecticide, was found to be moderately harmful to T. cacoeciae regarding mortality and slightly harmful regarding parasitism ratio. Our results are in confl ict with those reported by Thubru et al (2016), who found that surface contact toxicity of azadirachtin was Table 3. Parasitism ratio of Trichogramma cacoeciae on eggs of Ephestia cautella and longevity of adult females of the parasitoid, which survived 24 h exposure to dry residues of insecticides on glass plates treated at the recommended application rates.…”
Section: Sublethal Eff Ectssupporting
confidence: 91%
See 3 more Smart Citations
“…Azadirachtin, although a botanical insecticide, was found to be moderately harmful to T. cacoeciae regarding mortality and slightly harmful regarding parasitism ratio. Our results are in confl ict with those reported by Thubru et al (2016), who found that surface contact toxicity of azadirachtin was Table 3. Parasitism ratio of Trichogramma cacoeciae on eggs of Ephestia cautella and longevity of adult females of the parasitoid, which survived 24 h exposure to dry residues of insecticides on glass plates treated at the recommended application rates.…”
Section: Sublethal Eff Ectssupporting
confidence: 91%
“…Similar moderate to high toxicities of organophosphorus and synthetic pyrethroid compounds to adults of T. cacoeciae and other Trichogramma spp. have also been reported in other studies (Brunner et al, 2001, Youssef et al, 2004Jiu-Sheng et al, 2010, Zhu et al, 2009Abaar et al, 2011;Sohrabi and Amini, 2015;Thubru et al, 2016).…”
Section: Lethal Eff Ectssupporting
confidence: 81%
See 2 more Smart Citations
“…The brassicaceous ecosystems of Meghalaya harbour several natural enemies, many of them have a potential to reduce the pest damage (Firake et al, 2012a;Lytan and Firake, 2012;Firake et al, 2012b;Thubru et al, 2016). Among predators, the ladybird beetle, Coccinella septumpunctata Linnaeus (Coleoptera: coccinellidae) and syrphid flies, Episyrphus viridaureus (Wiedemann) and Betasyrphus isaaci (Bhatia) (Diptera: Syrphidae) are the major predators of mustard aphid in mid altitude hills of Meghalaya.…”
mentioning
confidence: 99%